Forming and Reforming the American Society of Missiology, 1973-2023 - Ireland, Daryl R. (Missiology, 2026)
The American Society of Missiology recently passed its 50th anniversary. That initiated a new history of the society, New Wineskins: Forming and Reforming the American Society of Missiology, 1973-2023, which argues that the vitality of the ASM waxes when its members seriously wrestle with what it means to be American, a society, and probe the meaning of missiology. Likewise, it wanes when those questions are temporarily resolved or ignored. As the ASM begins its sixth decade, an appreciation for this historical pattern may be a key to the society’s renewal.